Positive solutions of a three-point boundary-value problem for $\mathcal {p}$-Laplacian dynamic equation on time scales - Dogan, A. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 517.9We consider a three-point boundary-value problem for p-Laplacian dynamic equation on time scales. We show the existence at least three positive solutions of the boundary-value problem by using the Avery and Peterson fixed point theorem. The conditions we used here differ from those in the majority of papers as we know. The interesting point is that the nonlinear term $ f$ involves the first derivative of the unknown function. As an application, an example is given to illustrate our results.